2014
DOI: 10.1093/occmed/kqu044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unemployment on cardiovascular risk factors and mental health

Abstract: The patterns of major cardiovascular risk factors differed between unemployed and employed individuals in Poland. Our observations suggest employment status is a predictor of specific disease risk profiles; consequently, specific preventive measures are needed in unemployed individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
4
23
2
2
Order By: Relevance
“…there was a clear association between the employment situation and the prevalence of overweight and obesity. On the other hand, we con rm the results of Zagozdon et al [8] on cardio-vascular risk factors for smoking habits, with a higher percentage of people smoking more than 10 cigarettes a day. Although smoking constitutes a cardiovascular risk, analyzing the adjusted OR, there was no signi cant association between cardiovascular disorders and precarious work overall, although there is one among men.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…there was a clear association between the employment situation and the prevalence of overweight and obesity. On the other hand, we con rm the results of Zagozdon et al [8] on cardio-vascular risk factors for smoking habits, with a higher percentage of people smoking more than 10 cigarettes a day. Although smoking constitutes a cardiovascular risk, analyzing the adjusted OR, there was no signi cant association between cardiovascular disorders and precarious work overall, although there is one among men.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding BMI, Zagozdon et al [8], in a study on unemployment and health, found a signi cant association between being overweight and being unemployed, employing multivariate analysis. The nding that there was no difference in BMI in our study could be potentially explained by the nancial resources available during precarious work.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we adjusted for neighborhood unemployment, which has been shown in prior literature to be independently linked to both high rates of crime and poor health outcomes. 27,28 Similarly, we adjusted for English fluency as a proxy for immigration status, paying special attention to the Mexican immigrant communities on Chicago's South Side. Recent attention on immigration in the United States has led to growing awareness that immigrants are more likely to be victims of violent crime, related to underreporting because of fear of law or immigration enforcement.…”
Section: Discussionmentioning
confidence: 99%
“…We included all theoretically relevant confounders in final adjusted models, including aforementioned sociodemographic characteristics, clinic site, and neighborhood characteristics. Notably, we adjusted for neighborhood unemployment, which has been shown in prior literature to be independently linked to both high rates of crime and poor health outcomes . Similarly, we adjusted for English fluency as a proxy for immigration status, paying special attention to the Mexican immigrant communities on Chicago's South Side.…”
Section: Methodsmentioning
confidence: 99%
“…Ekonomiskās krīzes ietekme uz iedzīvotājiem tika novērota ne tikai Latvijā, bet arī citās valstīs. 2014. gadā tika publicēts pētījums (Zagożdżon, 2014), kuru veica, lai Polijas iedzīvotājiemun atsevišķi bezdarbniekiem -noskaidrotu kardiovaskulāro saslimšanu riska faktorus un depresijas simptomus. Kopumā pētījumā piedalījās 3052 bezdarbnieki un 2059 nodarbinātie.…”
Section: Bezdarbības Ietekme Uz Veselību Unemployment Influencing Healthunclassified